Feminism and New Men's Support for Gender Equality - Islam, Amaliyah Izzul; Kuswanti, Ana; Tayinapis, Radita Gora; Muqsith, Munadhil Abdul (Universitas Syiah Kuala, 2025)
This research examines the concept of